2018
DOI: 10.15171/jrip.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quality of life and adherence to treatment in hemodialysis patients

Abstract: Introduction: Institutionalizing adherence to treatment in hemodialysis patients is one of the important nursing goals for improving quality of life in these patients. Adherence to treatment approach in these patients can play a pivotal role in improving the health level and feeling of well-being. Objectives: This study aimed at determining the quality of life in hemodialysis patients presenting to hemodialysis centers affiliated to Shahid Beheshti University of Medical Sciences, Tehran, Iran, on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
2
11
1
2
Order By: Relevance
“…Likewise, a study conducted in Nepal showed that only 28.6% of HD pa ents were adhering 8 on medica on regimen. In the study demographic variables like educa on level, marital status, dura on of illness, and dura on of hemodialysis were significantly correlated with adherence to treatment which supports the study done in Tehran, 12,23,24 Malaysia, and from china.…”
Section: References Thapa D Et Alsupporting
confidence: 82%
“…Likewise, a study conducted in Nepal showed that only 28.6% of HD pa ents were adhering 8 on medica on regimen. In the study demographic variables like educa on level, marital status, dura on of illness, and dura on of hemodialysis were significantly correlated with adherence to treatment which supports the study done in Tehran, 12,23,24 Malaysia, and from china.…”
Section: References Thapa D Et Alsupporting
confidence: 82%
“…Emergency department (ED) nurses, in addition to enduring the pervasive mental and physical pressures in all wards of the hospital, face certain stresses such as dealing with the critical condition of the patient and the time urgency, which in turn causes negative emotions. (2) Quality of life (QOL) is a comprehensive concept that encompasses various aspects of life such as financial status, occupation, love, religion, as well as physical, mental, and social health, (3) but QoWL is a comprehensive program that enhances employee satisfaction, enhances learning in the environment, and helps them manage, change, and transform. (4) Etebari Aslet al showed in their study that 83.7% of nurses had a moderate QoWL and only 4.9% of them reported an optimal QoWL.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…In confirmation of the effectiveness of family-based education in the elderly, Tabari et al, (2019) as a result of their study, family-centered educational program has a positive effect on drug management of the elderly and can be used to improve the quality of education to patients, especially the elderly and Meridani et al, (2015) At the end of their study reported the positive effect of family-centered education on improving the care and control of diabetic elderly. Numerous studies have evaluated and confirmed the impact of this type of training on the elderly, including improving the laboratory parameters of patients with myocardial infarction (Dehkordi et al, 2021;Asgari et al, 2018;Keshavaraz et al, 2021) and improving adherence to the treatment regimen of patients undergoing hemodialysis (Chan et al, 2012;Naderifar et al, 2017;Naderifar et al, 2018), all of which confirm The usefulness of using family-centered education can be suggested by implementing it in hospitals to improve their implementation in order to improve the process of patient care.…”
Section: Discussionmentioning
confidence: 95%